The Comparative Analysis of the Performances of Four and Six Pole Pairs Permanent Magnet Synchronous Generator - Msuya, R. A.; Kainkwa, R. R.M.; Mgwatu, M. I. (Tanzania Journal of Engineering and Technology, 2019)
Wind power applications using multi-poles permanent magnet generators have become very attractive especially in small ratings. Low-speed multi-pole PM generators are maintenance-free and may be used in different climate conditions. Most of the low speed wind turbine generators presented is permanent magnet machines, which have advantages of high efficiency and reliability since there is no need of external excitation and conductor losses are removed from the rotor. From the study two types of PM AC generator are designed with 6 pole pairs and the other one with 4 pole pairs. These generators were designed and analysed using Maxwell software. The results were compared for the best performance determination. The 6 poles generator was found to have good power output with less Total Harmonic Distortion (THD) and high efficiency of over 92% that could be achieved at low wind speed of 2 m/s. Keywords: Comparisons, Performance, Permanent Magnet Wind Generator, Pole Pairs.